The influence of environmental factors on the population dynamics, reproductive biology and productivity of Echinogammarus marinus Leach (Amphipoda, Gammaridae) in the Mondego estuary (Portugal) - Maranhão, Paulo (2001)
The population density of Echinogammarus marinusin the Mondego estuary changed throughout the year, with a maximum during spring. The lowest densities were found in the north arm of the estuary, and the highest ones in the inner areas of the south arm. Higher densities appeared associated with the presence of muddy deposits under Fucus vesiculosus (Phaeophyta) and also with the presence of green macroalgae biomass over the sediments. Females were morphologically recognisable at smaller sizes than males, but males became larger than females. Fecundity increases with the size of females and is influenced by temperature and salinity. Sexual activity and recruitment take place continuously throughout the year, although it almost ceases by the end of winter. Present results are in opposition to the hypothesis of discontinuous recruitment presented in a previous study. Productivity (ash free dry weight- AFDW) was estimated at 1.74 to 2.45 g·m-2·year-1 in the north arm of the estuary corresponding to an annual turnover ratio () of 4.14 to 6.18. In the south arm, productivity was estimated at 1.96 to 2.74 g AFDW·m-2·year-1 in the middle section ( of 4.68 to 6.56), and at 3.85 to 5.38 g AFDW·m-2·year-1 in the innermost sampling area ( of 4.54 to 6.36). Differences in productivity appeared to depend only on population density, while annual ratios were similar over the estuary. Evidence was found that several features of E. marinus population dynamics were dependent on environmental factors resulting from the particular estuary hydraulic regime.